Clinical Predictive Factors for the Efficacy of Everolimus in Patients With Hormone Receptor-Positive, HER2-Negative Advanced Breast Cancer: A Multicenter Retrospective Cohort Study in Japan. (January 2019) - Kikawa, Yuichiro; Kotake, Takeshi; Kajiwara, Yukiko; Hashimoto, Kazuki; Yamashiro, Hiroyasu; Ohtani, Shoichiro; Takao, Shintaro; Toi, Masakazu
Purpose: To investigate the clinical predictive factors for the efficacy of everolimus (EVE) for advanced/metastatic breast cancer (AMBC). Methods: Routine practice data of consecutive patients with AMBC who received EVE at 5 institutions in western Japan were retrospectively analyzed in this cohort study (study registration no.: UMIN 000032569). The correlation among time to treatment failure (TTF), overall survival (OS), and clinical background was investigated via univariate and multivariate analyses using Cox hazards model for the clinically important variables. Results: A total of 134 patients were included in the analysis. The median TTF and OS were 5.2 months (95% confidence interval [CI]: 4.1-6.4) and 27.3 months (95% CI: 23.7-30.9), respectively. Multivariate analysis showed that dose reduction of EVE from any initial dose was associated with a longer TTF (hazard ratio [HR]: 0.52; 95% CI: 0.32-0.84, P = .007). Meanwhile, very low hormone sensitivity (ie, relapse within the first 2 years during adjuvant endocrine therapy or progression within 3 months of endocrine therapy immediately before EVE) was associated with a shorter TTF (HR: 2.48; 95% CI: 1.49-4.10, P < .001). In the analysis of stratified treatment outcomes, TTF was longer in the group with <3 liver metastases and in groups other than the very low hormone sensitivity group, regardless of the treatment line of EVE. Conclusions: Low hormone sensitivity and ⩾3 liver metastases were important prognostic factors for the efficacy of EVE. EVE may be less effective in patients with AMBC with these factors, and as such, chemotherapy should be administered instead.